Numerical investigation on a multi-channel micro combustor fueled with hydrogen for a micro-thermophotovoltaic system. (19th January 2021) - He, Ziqiang; Yan, Yunfei; Feng, Shuai; Li, Xiuquan; Fang, Ruiming; Ou, Zhiliang; Yang, Zhongqing
Abstract: Targeting at improving the energy output of the micro-thermophotovoltaic (MTPV) system, the heat transfer performance and energy output of the conventional micro combustor (CMC) and the multi-channel micro combustor (MCMC) with various channel shapes in the MTPV system are compared. The mean outer wall temperature of the MCMC with diamond channel is improved by 86.5 K than that of the CMC at the inlet hydrogen mass flow rate ( m ˙ i n, h y d r o g e n ) of 1.64 × 10-6 kg/s. Furthermore, four arrangements of MCMC are compared in this work. The double-layer MCMC with layers counterflow exhibits the highest total energy conversion efficiency of 13.2% when the m ˙ i n, h y d r o g e n is 8.10 × 10 −7 kg/s. The equivalence ratio (Φ) of premixed hydrogen/air plays a crucial role on the thermal performance of DMCMC-layer counter flow. The outer wall temperature and its uniformity becomes better as the equivalence ratio increases. The MPTV system with a DMCMC-layers counterflow can obtain an energy output of 19.3 W when the m ˙ i n, h y d r o g e n is 1.64 × 10-6 kg/s and Φ is equal to 1. Namely, the multi-channel micro combustor has the potential to be a novel energy resource for the MTPV system. Highlights: Compared the performances of conventional and multi-channel micro combustors. The influence of channel shapes on thermal performance is studied. The arrangements of multi-channel micro combustor are investigated. The influence of the equivalence ratio on thermal performance is studied.